Cervical fusion cage lattice structure optimization using computational biomechanics / Norish Mohamad Azhari ... [et al.] - Mohamad Azhari, Norish; Mohd Anuar, Mohd Afzan; Mazlan, Muhammad Hazli; Adenan, Mohd Shahriman; Mohd Miswan, Mohd Fairudz; Abdul Kadir, Mohammed Rafiq (Penerbit UiTM (UiTM Press), 2025)
Implants are instruments that typically inserted into a host tissue to restore any damaged physical function. In the case of a spinal implant, it usually consists of a spinal cage, pedicle screw and spinal rod, which they act together as a medical device that is implemented in the surgical treatment of patients with spinal diseases. Titanium alloy such as Ti-6Al4V is a biomaterial that commonly used in the spinal implants. However, the alloy is non-degradable and may cause stress shielding effect. Hence, magnesium alloy such as ZK60 is used as a substitute for the Ti-6Al-4V due to its biodegradable and bioabsorbable characteristics. The study aims to optimize the spinal cages of Ti-6Al-4V and ZK60 by incorporating lattice alteration to the implants and to evaluate the stress distribution of optimized spinal cages under sitting condition.